Public e-procurement: a research synthesis - Kassim, Erne Suzila; Hussin, Husnayati (2010)
In recent years, the number of publications dedicated to public e-procurement system, which is an application within the e-government, has been increasing. As public e-procurement systems cover and affect not only the issues of information systems, but also the concern of administration, economics, and social domain, they capture the interests of numerous studies to pursue a wide range of objectives. We therefore decided to survey the public e-procurement studies by using literature reviews and classification of articles from 1998 to 2008 with the main aim to investigate how the research has been developed during this period. Based on the articles, we classify the research into theories used, methodologies applied, and streams and scopes. From the findings, we offer suggestions on improving research in this field.